Methods of early revealing, prognosis of further course and complications of pollinosis. - N. D. Chukhrienko; Ye. G. Grabovskaya (Medičnì Perspektivi, 2013)
Under our observation there were 59 patients with pollinosis – 39 females and 20 males at the age from 18 to 68 years. All patients were in the phase of disease exacerbation. General clinical symptoms were: rhinitis, conjunctivitis and bronchial spasm. The results showed that first clinical manifestations appear in persons of young age. Half of the patients had aggravated allergologic anamnesis. Taking into account that pollinosis is a typical representative of diseases having mechanism of immunoglobulin E (IgE)-dependent allergic reactions of the first type, the authors have studied in detail level of IgE and its link with other factors. Practically in all patients with pollinosis level of total IgE exceeded the norm. As a result of studies performed, it was established that high IgE level, presence of phagocytosis defect and prolong duration of illness are the criteria which affect disease progress, aggravation of patients’ state, less efficacy of treatment. Due to the fact that development of bronchial obstruction and transformation of pollinosis into bronchial asthma is the most topical issue nowadays, the authors studied its link with other factors and findings. It was established that risk of pollinosis transformation into pollen bronchial asthma increases in the presence of high level of total IgE, aggravation of allergologic anamnesis, decrease of forced expiration volume (FEV), significant duration of disease course. In the course of investigation it was revealed that the highest efficacy of treatment is noted in patients receiving allergen-specific therapy; this confirms data of world scientific literature. The best treatment results are observed in pollinosis patients, with aggravated family history not in parents but in grandparents.